Lagu Anak Sebagai Repertoar Alternatif Pembelajaran Gitar Klasik Pada Anak Usia Sekolah Dasar - Whayan Christiana (JPKS (Jurnal Pendidikan dan Kajian Seni), 2018)
In general, the process of teaching classical guitar instruments in children still refer to the standard books that are sold in the market. In practice, children sometimes feel difficult in terms of mastery of the song both in terms of techniques and how to bring the song that causes them lazy or even not routine to practice. One strategy that is considered very telling is to use the repertoire of Indonesian children's songs. This strategy as one way to attract children in order to improve the skills of classical guitar playing. Emotionally, they (children) are certainly no stranger to children's songs. Thus, children will find it easier in the process of learning the classical guitar because it is so familiar to their ears compared to the classical songs in general that not necessarily all the children have heard it. Of course the child's song material as a learning material has been packaged into the classical guitar game.